Characterization of distinct molecular interactions responsible for IRF3 and IRF7 phosphorylation and subsequent dimerization. Issue 20 (22nd October 2020) - Dalskov, Louise; Narita, Ryo; Andersen, Line L; Jensen, Nanna; Assil, Sonia; Kristensen, Kennith H; Mikkelsen, Jacob G; Fujita, Takashi; Mogensen, Trine H; Paludan, Søren R; Hartmann, Rune
Abstract: IRF3 and IRF7 are critical transcription factors in the innate immune response. Their activation is controlled by phosphorylation events, leading to the formation of homodimers that are transcriptionally active. Phosphorylation occurs when IRF3 is recruited to adaptor proteins via a positively charged surface within the regulatory domain of IRF3. This positively charged surface also plays a crucial role in forming the active homodimer by interacting with the phosphorylated sites stabilizing the homodimer. Here, we describe a distinct molecular interaction that is responsible for adaptor docking and hence phosphorylation as well as a separate interaction responsible for the formation of active homodimer. We then demonstrate that IRF7 can be activated by both MAVS and STING in a manner highly similar to that of IRF3 but with one key difference. Regulation of IRF7 appears more tightly controlled; while a single phosphorylation event is sufficient to activate IRF3, at least two phosphorylation events are required for IRF7 activation.